Income Inequality by Gini-Coefficient on Suicide Death in Iran: A Review of National Data - Yousef VEISANI; Ali DELPISHEH; Reza VALIZADEH; Sattar KIKHAVANI (Tehran University of Medical Sciences, 2019)
Background: Research in source of inequality and enhance of knowledge can be reducing the inequalities in the coming decades. Therefore, we aimed to ascertain effects of income inequality measured by Gini-coefficient to death from suicide in Iran. Methods: This is an ecological study on the relation of Gini-coefficient and suicide death in Iran. Data were obtained from Iranian Urban and Rural Household Income for Gini-coefficient and Expenditure Survey and Iranian Forensic Medicine Organization for suicide. Concentration Index was used to determine of inequality by Gini-coefficient in suicide death and prediction model was applied by Stata software. Significant level considered less than 5%. Results: A Gini-coefficient between 0.2523 and 0.3755 (mean, 0.3092) was observed. The overall concentration index CI was -0.10 (95% CI= -0.19 to -0.01), therefore our results confirmed a positive inequality in incidence suicide rate result from income inequality in Iran. Conclusion: Our results showed a positive inequality due to Gini-coefficients in suicide death. This study could be a start for investigation of inequality source in geographical units and at the individual level in all provinces.